Review: Neuropathological features of unexplained sudden unexpected death in infancy: current evidence and controversies. Issue 4 (June 2014) - Paine, Simon ML; Jacques, Thomas S; Sebire, Neil J
<x xml:space="preserve">Abstract</x> Sudden infant death syndrome (SIDS) is a leading cause of postneonatal infant death in the developed world. The cause of SIDS is unknown but several hypotheses have been proposed, including the 'triple risk hypothesis', which predicts that foetal development of infants who subsequently succumb to SIDS is abnormal, leaving them unable to respond appropriately to stressors. Consistent with this hypothesis, a large number of studies have reported changes in the brain in SIDS. However, on nearly every subject, the reported findings vary widely between studies. Inconsistencies in the definitions of SIDS used and in control group selection are likely to underlie much of this variability. Therefore, in our analysis, we have included only those studies that met simple criteria for both the definition of SIDS and the control group. Of the 153 studies retrieved by our review of the literature, 42 (27%) met these criteria. Foremost among the findings reported by these studies are abnormalities of the brain stem, in particular brain stem gliosis and defects of neurotransmission in the medulla. However, these studies have not identified what could be considered in diagnostic terms a causative structural or biochemical abnormality for use in routine clinical practice. An assessment of changes in the architecture and composition of brain regions and changes in neurotransmission in multiple systems in a single, large cohort of well‐ and consistently characterized infants dying suddenly of a range of causes is needed before the inter‐relation of these different features can be appreciated.